Effecicacy of Transfer Factor Substance as a Growth Promoter in Nile Tilapia (Oreochromis niloticus) - Bunnajirakul, Sumrarn; Tipmongkolsilp, Nutcharnart (Journal of Mahanakorn Veterinary Medicine, 2018)
The current study was carried out to study the effecicacy of transfer factor substance as a growth promoter in Nile Tilapia (Oreochromis niloticus). One hundred and sixty Nile Tilapia, aged 21 days of an average of 6 centimeters body length and an average of 4 grams body weight (BW) were equally allocated into 4 treatment groups; 40 fishes per group (20 fishes with 2 replications). Fishes in each treatment group was fed with the transfer factor substance (TF) supplemented in diets at the level of 0 (control), 5, 10 and 100 mg/kg BW, respectively lasting for 40 days. At the end of the experiment, the BW and body length (BL) of the fishes in each group were measured and tissue samples (gill, liver and kidney) form the fishes in each group was collected and submitted for histopathological examination. The results have shown that the Nile Tilapia offered with 10 mg of TF/kg BW had the best BW at 9.14 ± 2.79 g, following with the BW of the fishes offered with 100, 5 and 0 mg of TF/kg BW as 8.65 ± 3.67 g, 8.33 ± 2.23 g and 8.03 ± 2.57 g, respectively and for the body length, there were 7.88 ± 0.89 cm, 7.88 ± 1.05 cm, 7.60 ± 0.82 cm and 7.90 ± 1.00 cm, respectively. Histological morphology of the studied tissues (gill, liver and kidney) of the fishes in each treatment group was not detected any significant morphological difference. Thus, the fishes received the TF had a tendency of better growth performance, compared with the fishes in the control group. Safety of TF usage was indirectly evaluated by histological examination of every group. There was non evidence of significant morphological change, especially in fishes offered with high level of TF (100 mg/kg BW)